TINJAUAN KRIMINOLOGI TERHADAP ANAK YANG MELAKUKAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - NANCI YOSEPIN SIMBOLON; TIMBUL RONI SITORUS; THEOPILUS LUCKYTA MELIALA; PHILIPUS WARUWU (JURNAL ILMIAH SIMANTEK, 2020)
Narcotics are substances or drugs derived from plants or non-plants, both synthetic and semi-synthetic, which can cause adecline or alteration of consciousness, loss of taste, reduce to pain relief, and can cause dependence, which is differentiatedinto groups as attached to the law. The factors that cause children to misuse narcotics are the factors of individuals, famil ies,economies, associations, social cultures, and others. The consequences of narcotics abuse the impact of drug abuse onphysical. Disorders of the nervous system (neurological) such as: seizures, hallucinations, impaired consciousness, nerveedge damage, disorders of the heart and blood vessels (cardiovascular). Efforts to prevent the misuse of narcotics give orinfuse early on the meaning of healthy living meanings.